Giving wasiat more than 1/3 to the wealth / Muhammad Irfan Imaduddin Azran … [et al.] - Azran, Muhammad Irfan Imaduddin; Ramli, Muhammad Adi Irfan; Sallehudin, Sadiq Najwan; Zuhairi, Muhammad Amir Iqbal; Hamzah, Amirul Khalis (2023)
A wasiat, also known as a will or testament, is a legal document that allows an individual to dictate how their assets and possessions should be distributed after their death. It serves as a means to ensure that one's wishes are respected, and their loved ones are provided for according to their desires and Islamic principles. (Abdul-Razzaq, 2021)